Characteristics of Hydrothermally Altered Wall Rocks from Modern Hydrothermal Fields - K. S. Lackschewitz; C. W. Devey (International Marine Minerals Society, 2006)
The mineralogy and geochemistry of hydrothermally altered wall rocks from different modern basaltic- and felsic-hosted hydrothermal fields at seafloor spreading centers and convergent margins have been studied to determine the characteristics of different types of alteration and to calculate the magnitudes of elemental exchanges between seawater and wall rock.